Direct evidence for high affinity blockade of NaV1.6 channel subtype by huwentoxin-IV spider peptide, using multiscale functional approaches. (1st May 2018) - Gonçalves, Tânia C.; Boukaiba, Rachid; Molgó, Jordi; Amar, Muriel; Partiseti, Michel; Servent, Denis; Benoit, Evelyne
Abstract: The Chinese bird spider huwentoxin-IV (HwTx-IV) is well-known to be a highly potent blocker of NaV 1.7 subtype of voltage-gated sodium (NaV ) channels, a genetically validated analgesic target, and thus promising as a potential lead molecule for the development of novel pain therapeutics. In the present study, the interaction between HwTx-IV and NaV 1.6 channel subtype was investigated using multiscale (from in vivo to individual cell) functional approaches. HwTx-IV was approximatively 2 times more efficient than tetrodotoxin (TTX) to inhibit the compound muscle action potential recorded from the mouse skeletal neuromuscular system in vivo, and 30 times more effective to inhibit nerve-evoked than directly-elicited muscle contractile force of isolated mouse hemidiaphragms. These results strongly suggest that the inhibition of nerve-evoked skeletal muscle functioning, produced by HwTx-IV, resulted from a toxin-induced preferential blockade of NaV 1.6, compared to NaV 1.4, channel subtype. This was confirmed by whole-cell automated patch-clamp experiments performed on human embryonic kidney (HEK)-293 cells overexpressing hNaV 1.1–1.8 channel subtypes. HwTx-IV was also approximatively 850 times more efficient to inhibit TTX-sensitive than TTX-resistant sodium currents recorded from mouse dorsal root ganglia neurons. Finally, based on our data, we predict that blockade of the NaV 1.6 channel subtype was involved in the in vivo toxicity of HwTx-IV, although this toxicity was more than 2 times lower than that of TTX. In conclusion, our results provide detailed information regarding the effects of HwTx-IV and allow a better understanding of the side-effect mechanisms involved in vivo and of channel subtype interactions resulting from the toxin activity. Highlights: HwTx-IV inhibits in vivo nerve-elicited compound muscle action potential in mice. HwTx-IV blocks in vitro nerve- and not directly-evoked mouse muscle contraction. HwTx-IV preferentially blocks TTX-S NaV subtypes overexpressed in HEK-293 cells. HwTx-IV is more potent to block TTX-S than TTX-R NaV channels of mouse DRG neurons.